Sleep quality and its association with waist circumference among undergraduate students - Nwoke, Chinenyenwa Violet; Mohamad, Marhazlina (Indonesian Nutrition Association, 2025)
Background: Poor sleep quality has been associated with metabolic disturbances and behavioural changes that promote obesity, with growing evidence linking inadequate sleep to increased central adiposity. Waist circumference (WC), a key indicator of abdominal fat and cardiometabolic risk, has also been implicated in disrupted sleep through mechanisms such as hormonal imbalance and sleep-disordered breathing. Exploring the relationship between WC and sleep quality among undergraduate students is important to better understand early risk factors for obesity and related health outcomes. Objective: This study aimed to examine sleep quality and its association with Body Mass Index (BMI) and Waist Circumference (WC) in an undergraduate population. Methods: A total of 277 undergraduate students from Universiti Sultan Zainal Abidin (UniSZA), Gong Badak Campus, Malaysia, aged 18 to 25 years, were recruited for this cross-sectional study using non-probability proportionate stratified sampling. The students were weighed, and their BMI and WC were measured. The Pittsburgh Sleep Quality Index (PSQI) was completed to assess sleep quality. Results: The results of the multiple linear regression analysis revealed that sleep quality did not significantly predict BMI (p>0.05). However, sleep quality significantly predicted WC (p=0.026), indicating a significant influence of sleep quality on WC. Conclusion: While sleep quality was not significantly associated with body mass index, it was significantly associated with waist circumference. These findings highlight the potential importance of promoting a consistent sleep schedule as a preventative strategy to enhance sleep quality and mitigate weight-related risks in undergraduate students.